2010
DOI: 10.1371/journal.pone.0009444
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Tolerance in Sleep Disorders

Abstract: BackgroundRecent epidemiological and experimental data suggest a negative influence of shortened or disturbed night sleep on glucose tolerance. Due to the high prevalence of sleep disorders this might be a major health issue. However, no comparative studies of carbohydrate metabolism have been conducted in clinical sleep disorders.Methodology/Principal FindingsWe performed oral glucose tolerance tests (OGTT) and assessed additional parameters of carbohydrate metabolism in patients suffering from obstructive sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 33 publications
6
21
0
2
Order By: Relevance
“…As reported by others as well, obstructive sleep apnea was predictive of somatic disorders in our model (4042). …”
Section: Discussionsupporting
confidence: 87%
“…As reported by others as well, obstructive sleep apnea was predictive of somatic disorders in our model (4042). …”
Section: Discussionsupporting
confidence: 87%
“…Keckels et al found no association between insomnia and impaired glucose metabolism. However, the mean TST in the insomnia group was greater than 5h, and no sub-group analysis was performed to compare TST below and above 5h 26 . In fact, an objective sleep duration of less than 5 h is necessary to increase the risk of diabetes 8,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, both short and long sleep durations may contribute to poor self-rated health by increasing fatigue. 46 Previous studies report that both short and long sleep duration are related to a number of adverse physiological changes, including impaired glucose tolerance, 47 inflammation, 48 and high uric acid levels, 49 which increase the risk of chronic diseases such as diabetes, obesity, and hypertension. 17 Conversely, short and long sleep duration could be a result of poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%